2022
DOI: 10.1177/10499091221108344
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Palliative and End of Life Care Interprofessional Education for Pre-licensure Healthcare Students: An Integrated Review

Abstract: An accelerating aging society and rise in serious illnesses has led to an increase in deaths and made the demand for palliative care even greater. An integrated review was conducted to identify the impact of interprofessional education (IPE) on palliative/end of life (EOL) care for unlicensed health care students with a multidisciplinary approach. The databases searched included MEDLINE, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Education Resources Information Center (ERIC), PsycINFO, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…However, only one to three individuals participated from each department; additionally, not all students were enrolled in the study. An integrated review examined studies about palliative care IPE for pre-licensure healthcare students and concluded that combined IPE and palliative/EOL interventions could potentially impact patient outcomes [9]. The review presented various teaching methods, such as simulation, role play, clinical experience, and case studies, but the review could not clarify the most effective teaching method.…”
Section: Introductionmentioning
confidence: 99%
“…However, only one to three individuals participated from each department; additionally, not all students were enrolled in the study. An integrated review examined studies about palliative care IPE for pre-licensure healthcare students and concluded that combined IPE and palliative/EOL interventions could potentially impact patient outcomes [9]. The review presented various teaching methods, such as simulation, role play, clinical experience, and case studies, but the review could not clarify the most effective teaching method.…”
Section: Introductionmentioning
confidence: 99%